Hedging housing risk in the new economy: is there a connection, and should firms care?. (4th August 2014) - Berg, Nathan
This paper analyses housing price dynamics in and outside of Telecom Corridor, a region near Dallas, Texas, with a high concentration of new economy firms. Using separate home price indexes in and outside this region, the paper tests whether home values are more volatile in the new economy area and compares mean–variance efficient portfolio weights on housing. The problem of hedging housing price volatility appears to be more severe in the high tech sector, suggesting that new economy firms may benefit by offering workers various forms of home price insurance in lieu of cash wages.